واقع ومعوقات استخدام معلمي التلاميذ الذين لديهم صعوبات التعلم للحاسب الآلي في غرفة المصادر - العبدالجبار، عبدالعزيز بن محمد; العثمان، سلطان بن إبراهيم بن محمد (مؤسسة التربية الخاصة والتأهيل, 2016)
هدفت هذه الدراسة إلى التعرف على واقع استخدام معلمي التلاميذ الذين لديهم صعوبات التعلم للحاسب الآلي في غرفة المصادر والمعوقات التي تحد من استخدامه، واستخدم الباحثان في هذه الدراسة المنهج الوصفي التحليلي وتكون مجتمع الدراسة من جميع معلمي التلاميذ الذين لديهم صعوبات التعلم والبالغ عددهم (224) معلما، الذين يعملون في المدارس الابتدائية الحكومية التابعة لإدارة التربية والتعليم في مدينة الرياض. وقد توصلت هذه الدراسة إلى النتائج التالية: 1- أبرز استخدامات معلمي التلاميذ الذين لديهم صعوبات التعلم للحاسب الآلي في غرفة المصادر، هي: إعداد الخطط التربوية الفردية، إعداد خطة سير العمل وتنظيمه في البرنامج، حفظ البيانات مراعاة لفقدانها أو تلفها، تسجيل التلاميذ. 2- أبرز المعوقات التي تحد من استخدام معلمي التلاميذ الذين لديهم صعوبات التعلم للحاسب الآلي، هي: شبكة الإنترنت غير متوافرة في برامج صعوبات التعلم، وعدم توافر أجهزة الحاسب الآلي في البرنامج منذ تأسيسه، وقلة المخصصات المالية تحول دون تامين أجهزة الحاسب الآلي، ولا تتوافر برامج الحاسب الآلي التعليمية المناسبة للتلاميذ.
This study aims to identify the reality of how teachers of students of learning disabilities use computers in the resource room, and all obstacles that may limit its usage, Also, the researcher of this study used the descriptive analytical method, for describing the usage of the teachers of students of learning disabilities for computers in the resource room, and the obstacles that may limit its usage, The study community evolved including all the student’s teachers who have a learning disability, they are abut (224) teachers, who works in the governmental primary schools of the department of education in Riyadh. The findings of this study reached the following mentioned results: The most prominent use for the teachers of the students of learning disability for computer in the resource room is as follows: using the computer for the preparation of the individual educational plans, also the computer is being used for preparing a plan workflow and to organize it into the program, and he uses computer for saving data from being damaged or lost, also uses computer for` enrolling the students. The most prominent obstacles which could limit the computer use for the teacher of the students who has learning disabilities are that: the internet network is not available in the programs of learning disability, there are not an available computers in the program since it is being established, also lacking of the financial allocations prevent from having any computers, and that it is not available any suitable educational computer programs for students.
Keywords: طرق التدريس -- صعوبات التعلم -- الحاسب الآلي -- غرفة المصادر